Structural basis for dsRNA recognition and interferon antagonism by Ebola VP35 - Leung, Daisy W. (2010)
The VP35 protein encoded by the highly pathogenic Ebola virus facilitates immune evasion by antagonizing antiviral signaling pathways, including those initiated by RIG-I like receptors. Here we report the crystal structure of Ebola VP35 interferon inhibitory domain (IID) bound to short double-stranded RNA (dsRNA), which reveals how VP35-dsRNA interactions contribute to immune evasion, and corresponding in vivo studies. Conserved basic residues in VP35 IID recognize the dsRNA backbone, whereas the dsRNA blunt ends are “end-capped” by a pocket of hydrophobic residues that mimics blunt end dsRNA recognition by RIG-I-like receptors. Residues that are critical for RNA binding are also important for interferon inhibition in vivo, but not for viral polymerase co-factor function of VP35. These results suggest that simultaneous recognition of dsRNA backbone and blunt ends provides a mechanism by which Ebola VP35 antagonizes host dsRNA sensors and immune responses.